2006
DOI: 10.1176/ajp.2006.163.12.2080
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Second-Generation Antipsychotics and Perphenazine in a Randomized Trial of Treatment for Chronic Schizophrenia

Abstract: Treatment with perphenazine was less costly than treatment with second-generation antipsychotics with no significant differences in measures of effectiveness. However, the trial was limited by a high dropout rate, and longer-term neurological and metabolic side effects require further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
156
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(163 citation statements)
references
References 25 publications
6
156
0
1
Order By: Relevance
“…However, most of cost studies in this field often fail to link costs to outcomes of care, and they do not necessarily specify the cost of psychopharmacological drug use. In the face of recent doubts about the cost-effectiveness of second-generation antipsychotics informed by controversial findings from various trials and meta-analyses (Rosenheck, 2006;Rosenheck et al, 2006;Jones et al 2006;Davies et a.l. 2008;Zhu et al 2008;Carpenter & Buchanan 2008), quantitative data in this field are fundamental to the ongoing transformation of community care systems.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of cost studies in this field often fail to link costs to outcomes of care, and they do not necessarily specify the cost of psychopharmacological drug use. In the face of recent doubts about the cost-effectiveness of second-generation antipsychotics informed by controversial findings from various trials and meta-analyses (Rosenheck, 2006;Rosenheck et al, 2006;Jones et al 2006;Davies et a.l. 2008;Zhu et al 2008;Carpenter & Buchanan 2008), quantitative data in this field are fundamental to the ongoing transformation of community care systems.…”
Section: Introductionmentioning
confidence: 99%
“…It is a warning claim that 90 % of trials showed superiority of the sponsor's drug [18] what can explain "Why olanzapine beats risperidone, risperidone beats quetiapine, and quetiapine beats olanzapine" [ 19]. Several large independent studies like CATIE (Clinical Antipsychotic Trials of Intervention Eff ectiveness), CUtLASS (Cost Utility of the Latest Antipsychotic Drugs in Schizophrenia), and EUFEST (European First Episode Study) have found that the new generation antipsychotics are no more eff ective, no better tolerated and are less cost eff ective than their old generation predecessors [20,21,22,23]. Some independent meta-analyses pooling unpublished as well as published data indicated that SSRIs were no more eff ective than placebo in treating mild-to-moderate depression [24,25].…”
Section: Volume 4 • Number 2 • May 2017 • Hophmentioning
confidence: 99%
“…While patients stayed on olanzapine longer than other medications 2 there were no significant advantages for any atypical as compared to perphenazaine on measures of symptoms, 3 neurologic side effects, 2 neurocognition, 4 quality of life, 5 employment, 6 or violent behavior. 7 Patients assigned to perphenazine were more likely to change medications due to extrapyramidal symptoms (EPS) but there was no significant difference between perphenazine and any atypical antipsychotic on the broader measure of time to discontinuation'for any adverse effect or on standard measures of neurological side effects, and the difference in discontinuation for EPS was small (8% for perpehanzine vs 4% for ziprasidone and 2% for olanzapine).…”
mentioning
confidence: 95%